Characteristics and Outcomes of Parkinson's Disease Individuals Hospitalized with COVID‐19 in a New York City Hospital System. Issue 7 (30th July 2021) - Nwabuobi, Lynda; Zhang, Cenai; Henchcliffe, Claire; Shah, Hiral; Sarva, Harini; Lee, Andrea; Kamel, Hooman
ABSTRACT: Background: The coronavirus disease 2019 (COVID‐19) pandemic has caused worse health outcomes among elderly populations with specific pre‐existing medical conditions and chronic illnesses. There are limited data on health outcomes of hospitalized Parkinson's disease (PD) individuals infected with COVID‐19. Objectives: To determine clinical characteristics and outcomes in hospitalized PD individuals infected with COVID‐19. Methods: Individuals admitted to NewYork‐Presbyterian with a diagnosis of PD were retrospectively identified using an electronic medical record system. Clinical characteristics and mortality were abstracted. Results: Twenty‐five individuals with PD, mostly male (76%) with a median age of 82 years (IQR 73–88 years), were hospitalized for COVID‐19 infection. A total of 80% of individuals had mid‐stage to advanced PD (Hoehn and Yahr 3–5) and 80% were on symptomatic pharmacologic therapy, most commonly levodopa (72%). The most common comorbidities were hypertension (72%) and mild cognitive impairment or dementia (48%). A total of 44% and 12% of individuals presented with altered mental status and falls, respectively. Mortality rate was 32% compared to 26% for age‐matched controls ( P = 0.743). Individuals who died were more likely to have encephalopathy during their admission (88% vs. 35%; P < 0.03). Conclusion: PD individuals who require hospitalization for COVID‐19 infection are likely to be elderly, have mid‐stage to advanced disease, and be on pharmacologic therapy. Hypertension and cognitive impairment are common comorbidities in these individuals and encephalopathy during hospitalization is associated with risk of death. Altered mental status and falls are clinical presentations of COVID‐19 infection in PD that clinicians should be aware of. A diagnosis of PD is not a risk factor for COVID‐19 mortality.